Linux bible - Negus, Chris (Wiley, 2012)
Linux Offers a complete restructure, complete with exercises, to make the book a better learning tool * Places a strong focus on the Linux command line tools and can be used with all distributions and versions of Linux * Features in-depth coverage of the tools that a power user and a Linux administrator need to get started. This practical learning tool is ideal for anyone eager to set up a new Linux desktop system at home or curious to learn how to manage Linux server systems at work.